Meningkatkan Prestasi Belajar Siswa dengan Model Examples Non-Examples pada Pelajaran Matematika Materi Bangun Datar Kelas 1 SD Negeri Semarangan 1 - Ariffia, Citrani Natha; Kurniawati, Wahyu; Purnomo, Heru (Universitas Muhammadiyah Magelang, 2025)
The purpose of this study is to improve critical thinking skills and maximum learning outcomes through examples non examples learning model. Learning that involves students actively encourages their creativity is one of success in learning. This research uses Classroom Action Assessment (PTK) research with the Examples Non Examples learning model is one of the learning methods that can be applied in the learning process. This article aims to explain the application of the Examples Non Examples model in Mathematics learning with a focus on flat building material, and how this model can increase student creativity